International Meeting 40 years of the 1980 Azores Earthquake, 6th - 7th October 2020 - Conference Report - Fontiela, João (2020)
The main goal of the International Meeting “40 Years of the 1980 Azores Earthquake” was promoting a reflection of the earthquake of January 1st, 1980, and the advances since them on topics like seismology, seismic hazard, and risk, building rehabilitation and public policies. Nevertheless, due to the COVID-19 outbreak, the organizing committee decided that the meeting should be online and re- arrange the strategy, reduce the scientific program, and canceled the social one. The scientific program had five sessions, with six keynotes, 16 presentations, round table beyond the opening ceremony. All the sessions were live-streamed and available at https://azores4080meeting.wordpress.com as well as the proceedings and program. Instituto Superior Técnico, Universidade dos Açores and Universidade de Évora handled the organization of the conference.